ICL (Encyclopedia of Ophthalmology, 2018)
Background Interstitial keratitis is a classic manifestation of late congenital syphilis, typically presenting in childhood or adolescence. Adult-onset presentation is rare and poses a diagnostic and therapeutic challenge, particularly in patients without a known history of congenital infection. Case report We report a 28-year-old man with an 11-year history of progressive bilateral ocular redness, tearing, and visual decline who was found to have bilateral interstitial keratitis with positive treponemal and negative nontreponemal serologies, consistent with late congenital syphilis. Despite treatment with intravenous penicillin G and adjunctive topical corticosteroids, the clinical course was complicated by refractory inflammation, progressive stromal scarring, corneal thinning, and perforation requiring tectonic patch grafting. Recurrent inflammatory flares persisted despite sustained steroid therapy and negative nontreponemal serologies. Visual rehabilitation required prolonged multidisciplinary management with rigid corneal and scleral contact lenses. Conclusion This case highlights the diagnostic and therapeutic complexity of adult-onset presumed congenital syphilitic interstitial keratitis. In cases where a definitive diagnosis cannot be confirmed, close collaboration among infectious disease, ophthalmology, and optometry is needed to navigate treatment decisions, manage refractory inflammation, and guide visual rehabilitation. This case demonstrates that specialty contact lens fitting and sustained interdisciplinary care are essential in restoring functional vision.